Incontinentia pigmenti in neonate: a case report - Putu Gde Hari Wangsa; Luh Made Mas Rusyati; I Gusti Ayu Agung Dwi Karmila; Ni Luh Putu Ratih Vibriyanti Karna; Ketut Wida Komalasari; Made Hermina Laksmi (Intisari Sains Medis, 2022)
Background: Incontinentia pigmenti (IP) is a rare X-linked dominant inherited genodermatosis that occurs almost in females and is usually accompanied by other ectodermal tissue diseases such as the central nervous system, eyes, hair, nails, teeth and skeletal system. This case report aims to enhance understanding of incontinentia pigmenti and provide appropriate treatment to patients and proper education to families. Case report: A 3-days-od baby girl was consulted by the Pediatric department with complaints of blisters and erythematous rashes on almost her entire body with the Blaschko line distribution. The nails on the right and left big toes appeared inward. No history of fever and seizure. No family had similar complaints. There were no eye and nerve abnormalities involved. She treated with hydrocortisone 1% cream every 12 hours on erythematous papules and vesicles, open compresses with 0.9% NaCl every 8 hours for 10-15 minutes on lesions with yellowish crusts. Thus, the patient diagnosed with incontinentia pigmenti. Conclusion: The diagnosis of incontinentia pigmenti is based on history and physical examination. This case is very rare, so the family needs to understand the course of this disease. Appropriate management and education can prevent secondary infection.